Non-invasive assessment of portal hypertension using quantitative magnetic resonance imaging - Palaniyappan, Naaventhan; Cox, Eleanor; Bradley, Christopher; Scott, Robert; Austin, Andrew; O’Neill, Richard; Ramjas, Greg; Travis, Simon; White, Hilary; Singh, Rajeev; Thurley, Peter; Guha, Indra Neil; et al. (Elsevier, 2016)
Background & Aims